Legal Protection Against Consumers Experiencing Price Differences Between Labels Prices and Self-Service Cashiers in the District Sleman - Vicki Dwi Purnomo; Jumadi (Formosa Journal of Social Sciences (FJSS), 2023)
The number of cases of price difference between the price tag and the self-service cashier, especially in Banyuwangi Regency, of course, is proof that the consumer's right to obtain goods at the promised exchange rate is in accordance with Article 4 Paragraph 2 Constitution Protection Consumer has violated. Based on the problems above, the author formulates problems related to how the form of accountability from supermarkets in problem difference price between label price And machine cashier Which experienced by consumers? The results of the study concluded that the implementation of legal protection for consumers who suffered losses due to cases of price differences between price tags and supermarket cashiers in the district Sleman fall into the criminal element.